2007
DOI: 10.1093/jac/dkl490
|View full text |Cite
|
Sign up to set email alerts
|

A novel ex vivo skin model to study the susceptibility of the dermatophyte Trichophyton rubrum to photodynamic treatment in different growth phases

Abstract: We demonstrated that the PDT susceptibility of T. rubrum depended on the time of PDT application after spore inoculation. A decrease in susceptibility was observed with increasing time of PDT application for both photosensitizers in DMEM. Changing the incubation medium to distilled water resulted in an increased fungicidal effect for Sylsens B and in a decreased effect for DP mme. We conclude that T. rubrum is susceptible to PDT in a situation that mimics the clinical situation. The fungicidal effect of PDT on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 16 publications
0
48
0
1
Order By: Relevance
“…In line with this assumption, previous studies of reconstituted human epithelia infected with C. albi- cans revealed that supplementation of the model with polymorphonuclear leukocytes strongly impaired tissue invasion by this pathogenic yeast (22). In the past, various in vitro models using reconstituted epidermis or skin explants have been established and were also proven successful for the analysis of dermatophytosis (1,2,5,7,19,20,24,26). Nevertheless, the commercially available RHE model, which was employed in the present study for the analysis of A. benhamiae mutants, may further advance the research of dermatophytosis and the identification of basic virulence attributes of dermatophytes.…”
Section: Discussionmentioning
confidence: 82%
“…In line with this assumption, previous studies of reconstituted human epithelia infected with C. albi- cans revealed that supplementation of the model with polymorphonuclear leukocytes strongly impaired tissue invasion by this pathogenic yeast (22). In the past, various in vitro models using reconstituted epidermis or skin explants have been established and were also proven successful for the analysis of dermatophytosis (1,2,5,7,19,20,24,26). Nevertheless, the commercially available RHE model, which was employed in the present study for the analysis of A. benhamiae mutants, may further advance the research of dermatophytosis and the identification of basic virulence attributes of dermatophytes.…”
Section: Discussionmentioning
confidence: 82%
“…at room temperature (RT). Microconidia suspensions were prepared as described previously and stored in liquid nitrogen for no longer than 6 months [9,10]. Counting the number of colony forming units (cfu) on malt extract agar (MEA, Oxoid, Hampshire, UK) was used as a viability check.…”
Section: Chemicalsmentioning
confidence: 99%
“…Hence, tinea capitis, tinea barbae, tinea corporis, tinea manum, tinea cruris, tinea pedis, and tinea unguium refer to dermatophytic infections of the scalp, beard, body, hands, inguinal folds, feet, and nails, respectively. Together, these infections affect at least 10% of the US population at any given time [1,2].…”
Section: Introductionmentioning
confidence: 99%